Implementation of Technology-Based K3 System to Improve Occupational Safety in Companies - Dongoran, Johnson; Dwi Nugroho, Gigih Rirudro (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2025)
Workplace accidents in Indonesia have shown a consistent rise, with 234,270 cases recorded in 2021, emphasizing the need for improved safety measures. This study investigates the impact of implementing technology-based Occupational Safety and Health (OSH) systems at PT. Sinar Makmur Semarang, utilizing a qualitative descriptive approach with interviews and documentation. Findings reveal that while technology like CCTV and personal protective equipment has enhanced safety, challenges such as employee compliance and technological maintenance remain. The study contributes practical recommendations for adopting technology-driven OSH systems and theoretical insights for future research in industrial safety.